Nüfusun ve Yerleşmelerin Yükseltiye Göre Değişimi: Muş İli Örneği - Dölek, İskender; Avcı, Vedat; Harunoğulları, Muazzez (My University, 2018)
Muşilinin de içerisinde yer aldığı Doğu Anadolu Bölge’sinin, ekonomisi tamameninsan gücü ile ayakta durmaktadır. Bu açıdan nüfusunun mekAn üzerindekidağılışı ve bu dağılışı etkileyen faktörlerin ortaya konması oldukça önemlidir.Muş ilinde nüfusun %1’inin 1000-1250 m, % 69’unun 1251-1500 m, % 25’inin1501-1750 m, % 4’ü nün 1751-2000 m, % 1’inin ise 2001-2250 m yükselti basamağıaralığında, yerleşmelerin % 2’sinin 1000-1250 m, % 39’unun 1251-1500 m, %39’unun 1501-1750 m, % 17’sinin 1751-2000 m, % 3’ünün ise 2001-2250 m yükseltiaralığında yer aldığı belirlenmiştir. Muş ilinde sanayi ve makineleşmeye bağlıbir gelişim diretmesinden ziyade yayla, mağara, ekolojik, termal turizm, dağsporları (kayak) gibi ilde var olan potansiyele dayalı aktivitelere yoğunlaşmasınınilin gelişimi açısından daha gerçekçi olacağı düşünülmektedir.

Theeconomy of Eastern Anatolia Region, where Muş province is located, dependscompletely on human power. In this sense, it is significant to reveal thedistribution of the population by space and the factors affecting thisdistribution. In Muş province, the distribution of population was detected as1% at 1000-1250 m, 69% at 1251-1500 m, 25% at 1501-1750 m, 4% at 1751-2000 mand 1% at 2001-2250 m elevation step and distribution of settlements wasdetected as 2% at 1000-1250 m, 39% at 1251-1500 m, 39% at 1501-1750 m, 17% at1751-2000 m and 3% at 2001-2250 m elevation range. It is believed that theconcentration of activities based on the current potential such as highland,cave, ecological, thermal tourism, mountain sports (skiing) is more realisticin terms of the development of Muş province instead of insisting on thedevelopment based on industry and mechanization.
Change of Population and Settlement by Elevation: Sample of Muş Province
Keywords: Coğrafya; Nüfus İstatistikleri Bilimi